Design of an eye-detection experiment using frequency modulated continuous wave (FMCW) radar - AR Subbu Adaikalavan (Nanyang Technological University, 2020)
Sleep has always been an essential activity for human health. Many nervous system disorders such as Parkinson’s Disease, Post Traumatic Stress Disorders have been developed progressively from sleep disorders. Hence it is imminent to identify these disorders and Rapid Eye Movement Disorder (RBD) is a common symptom for these diseases and can be identified during our sleep pattern. Till date the proven methodology to detect RBD is through polysomnography, with the use of detection of electrical activity in our brain while a sleep. However, because it does not provide good comfort to the sleep due to the placement of various electrodes all over the body, the study has always been not accurate. This project will explore the possibility of Frequency Modulated Continuous Wave (FMCW) Radar to detect the REM, which is a symptom to RBD, contactless to the human body. FMCW Radar is also known to detect close range movements with high accuracy. Hence this research project will aim to prove the usability of FMCW Radar to detect REM without any contact. To prove the feasibility, the project will adopt the vital signs experiment and apply to the use of eye movement detection. The thesis is written on a step by step basis of the key experiments to conduct based on expected results and assumed predictions.